Microstructure-tunable highly conductive graphene–metal composites achieved by inkjet printing and low temperature annealing. (31st January 2018) - Zhao, Jie; Song, Man; Wen, Chenyu; Majee, Subimal; Yang, Dong; Wu, Biao; Zhang, Shi-Li; Zhang, Zhi-Bin
Abstract: We present a method for fabricating highly conductive graphene–silver composite films with a tunable microstructure achieved by means of an inkjet printing process and low temperature annealing. This is implemented by starting from an aqueous ink formulation using a reactive silver solution mixed with graphene nanoplatelets (GNPs), followed by inkjet printing deposition and annealing at 100 °C for silver formation. Due to the hydrophilic surfaces and the aid of a polymer stabilizer in an aqueous solution, the GNPs are uniformly covered with a silver layer. Simply by adjusting the content of GNPs in the inks, highly conductive GNP/Ag composites (>10 6 S m −1 ), with their microstructure changed from a large-area porous network to a compact film, is formed. In addition, the printed composite films show superior quality on a variety of unconventional substrates compared to its counterpart without GNPs. The availability of composite films paves the way to the metallization in different printed devices, e.g. interconnects in printed circuits and electrodes in energy storage devices.